2014
DOI: 10.1073/pnas.1404357111
|View full text |Cite
|
Sign up to set email alerts
|

p53 constrains progression to anaplastic thyroid carcinoma in a Braf -mutant mouse model of papillary thyroid cancer

Abstract: Anaplastic thyroid carcinoma (ATC) has among the worst prognoses of any solid malignancy. The low incidence of the disease has in part precluded systematic clinical trials and tissue collection, and there has been little progress in developing effective therapies. v-raf murine sarcoma viral oncogene homolog B (BRAF) and tumor protein p53 (TP53) mutations cooccur in a high proportion of ATCs, particularly those associated with a precursor papillary thyroid carcinoma (PTC). To develop an adult-onset model of BRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 33 publications
(50 reference statements)
4
117
0
2
Order By: Relevance
“…EMT is the first step in metastasis, which is characterized by the loss of epithelial polarity and cell-cell adhesion and is a precursor to increased cell mobility. MAPKs are involved in cell migration and invasion, partially through regulation of focal adhesion kinase (FAK) and matrix metalloproteinases (MMPs) [36-38]. Previous studies have indicated that ROS could regulate PI3K/Akt and MAPK signaling pathways and thus be involved in apoptosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is the first step in metastasis, which is characterized by the loss of epithelial polarity and cell-cell adhesion and is a precursor to increased cell mobility. MAPKs are involved in cell migration and invasion, partially through regulation of focal adhesion kinase (FAK) and matrix metalloproteinases (MMPs) [36-38]. Previous studies have indicated that ROS could regulate PI3K/Akt and MAPK signaling pathways and thus be involved in apoptosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…We do know that mutant BRAF-mediated inhibition of iodine transport is only partially ERK dependent, inhibition of the MAPK pathway with a BRAF or MEK inhibitor does not completely restore iodine uptake, and the effects of either RAF or MEK inhibitors on downstream signaling in thyroid cancer cells may be limited by feedback mechanisms (15,16,23). An important area of future investigation will be to study BRAF inhibitors in combination with other inhibitors of the MAPK or feedback pathways to achieve even more robust radioactive iodine uptake in BRAF V600E-mutant, iodine-refractory PTC (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68][69] In the recent past, a number of transgenic mice have been developed that mimic ATC in vivo [70][71][72][73] and serve as much more clinically relevant models for preclinical testing. These models have primarily been used to elucidate the hypothesis that ATCs arise as a progression from PTC or FTC due to hits to multiple signaling pathways and therefore provide the closest simulation environment reflective of direct in human testing.…”
Section: Preclinical and Clinical Studies Evaluating Potential Therapiesmentioning
confidence: 99%